A magnetoelastic bone fixation device for controlled mechanical stimulation at femoral fractures in rodents. (20th August 2021) - Karipott, Salil S; Fear, Karly; Nelson, Bradley; Leguineche, Kelly; Lin, Angela; Shekhar, Sudhanshu; Guldberg, Robert E; Ong, Keat Ghee
Abstract: Studies have shown that mechanical stimulations can provide anabolic bone formation and counteract conditions such as osteoporosis in intact bones, as well as promote healing of bone fractures. However, many of these studies are based on external mechanical loading platforms or bulky wearable force loading systems, which are inconvenient and impractical in clinical settings especially for the treatment of bone injuries. To overcome this limitation, a bone fixation device was developed to provide localized mechanical strains across a bone fracture site. The fixation device, designed for a rodent's femoral fracture (critical-size segmental defect), is consisted of a magnetoelastic (ME) actuator that changes its physical dimension when exposed to magnetic fields. The strain produced by the ME actuator is transferred to the bone fixation device, which acts directly on the bone-implant interface to produce a highly focused and localized mechanical loading. The actuation generated by the fixation device was evaluated, and results show the device was able to provide up to 150 με at 30 Hz. Mechanical characterization of the fixation device showed its off-axis compressive stiffness was higher than 160 N mm −1, which was comparable to existing fixation devices used for the same rodent's femoral fracture model. Furthermore, the fixation device was implanted in rodent subjects for 8 weeks to validate its safety and biocompatibility in vivo . Results indicate the device is biocompatible, showing no adverse impact on bone regeneration.